Design of automatic tekong launcher system using progressive methods - Muhammad Adib, Shaharun; Tarmizy, Che Kar; Sazali, Salleh; Wan Hassan, Wan Hamat; Mohd Idzwanrosli, Mohd Ramli (Penerbit UMP, 2024)
The Automatic Tekong Launcher System represents a cutting-edge advancement in sepak takraw equipment, seamlessly blending precision engineering with advanced automation to transform the role of the Tekong. At its foundation, the system is built from durable aluminum profiles, ensuring a robust and reliable structure. The launcher mechanism is crafted using CNC milling technology, reflecting a commitment to precision and optimal performance. Central to the system’s operation is a power supply, featuring three 30A AC to DC converters that provide consistent electricity to the motors. These motors include four high-speed 24V DC units and two stepper motors, capable of reaching speeds up to 2800 rpm. This setup allows for meticulous control over the ball's speed and trajectory, essential for precise launches. The brain of the system is a Programmable Logic Controller (PLC), which manages the intricate movements of both motors and sensors, enabling the automation of ball launching with minimal human intervention. For added versatility, the system incorporates joystick control, allowing for semi-automatic operation that enhances user interaction and adaptability to various gameplay scenarios. By integrating advanced automation, precision engineering, and a modular design, the Automatic Tekong Launcher System offers unparalleled performance in both training and competitive environments. Its ability to deliver consistent, accurate launches elevates the standard of sepak takraw, making it a revolutionary tool for players and coaches aiming to refine their skills and strategies.